Implementation of Problem-Based Learning to Enhance Students’ Higher Order Thinking Skills and Interest in Global Warming Material - Kurniawan, Aris; Wiyatmo, Yusman; Putri, Utami; Naba, Sul Daeng; Dua Padang, Veronika (Universitas Lambung Mangkurat, 2025)
This study aims to determine how implementing the problem-based learning (PBL) model has improved students' higher-order thinking skills (HOTS) and their interest in global warming material. This study employed a descriptive method intended to accurately describe a variable, phenomenon, or condition as it exists. A one-group pretest-posttest design was used in this study, with one classroom serving as the sample. The sample for this study was selected from class X-E of SMAN 1 Ngaglik in the 2023/2024 academic year, which consisted of 31 students, using a lottery-based random sampling method. A HOTS test was administered to measure the abilities in analysis, evaluation, and creation defined in Bloom's taxonomy to collect data. Furthermore, participants were required to submit an interest questionnaire. The interest questionnaire used indicators of interest, including 1) student interest, 2) the feeling of pleasure, 3) student involvement, and 4) student attention. Students' HOTS on global warming material showed a significant improvement, with an N-gain score of 0.67 and scores rising from 54.84 to 85, classified as moderate. Students' interest in global warming material increased from a score of 37.76 to 78.71, with an N-gain score of 0.66, also categorized as moderate. The results of the paired sample t-test on HOTS and student interest showed the same result, namely, Sig (2-tailed) value of 0.000 < 0.05. The paired t-test results and the percentage of normalized gain score, show that the PBL model can be used to significantly enhance students' HOTS and interest in global warming material. The results of this study provide teachers with practical suggestions for establishing innovative, meaningful, and rich learning environments that foster students' intellectual curiosity and improve their HOTS.